2022
DOI: 10.1037/apl0000957
|View full text |Cite
|
Sign up to set email alerts
|

When leader self-care begets other care: Leader role self-compassion and helping at work.

Abstract: Integrating research on self-compassion with leader identity theory, we propose that leader role self-compassion—a mindset in which a leader takes a supportive, kind, and nonjudgmental stance toward himself or herself in relation to challenges faced in a leader role—matters for subsequent leader behaviors and stakeholder perceptions by strengthening leader identity. To test these theoretical ideas, we developed and tested a leader role self-compassion intervention in two field experiments. In the first field e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 107 publications
(161 reference statements)
1
27
0
Order By: Relevance
“…The self-regulatory effects of self-compassion may apply more broadly to all employees, as we find beneficial effects for this mindset in a sample of workers across a broad range of industries and job levels. Thus, taken together, our work and the work of Lanaj et al (2021) suggest that self-compassion may be beneficial for fulfilling role responsibilities at work, but that the contextualization of self-compassion may matter. For leaders, tying self-compassion to their leader role seems to benefit work performance through leader identity.…”
Section: Theoretical and Practical Implicationsmentioning
confidence: 69%
See 3 more Smart Citations
“…The self-regulatory effects of self-compassion may apply more broadly to all employees, as we find beneficial effects for this mindset in a sample of workers across a broad range of industries and job levels. Thus, taken together, our work and the work of Lanaj et al (2021) suggest that self-compassion may be beneficial for fulfilling role responsibilities at work, but that the contextualization of self-compassion may matter. For leaders, tying self-compassion to their leader role seems to benefit work performance through leader identity.…”
Section: Theoretical and Practical Implicationsmentioning
confidence: 69%
“…For example, our work shares a focus with the work of Lanaj et al. (2021) in examining how self‐compassion can be an asset for performance at work. Lanaj et al.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Research on leadership has also found that self-compassionate leaders are perceived as more competent and politer [82].…”
Section: Self-compassion: a Recent Interest For An Ancient Practicementioning
confidence: 99%